2021
DOI: 10.1002/ppul.25650
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID‐19 infection in pediatric pulmonary hypertension: A single‐center experience

Abstract: Background: The global COVID-19 pandemic was particularly concerning for the pediatric pulmonary hypertension (PH) population due to immature immune systems and developmental comorbidities. This study aims to describe a single-center experience of pediatric PH patients diagnosed with COVID-19 disease. Methods: A retrospective cohort study of all pediatric patients followed by the PH Center at Texas Children's Hospital diagnosed with COVID-19 infection from April 2020 to February 2021. Results: We identified 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There have been some previous reports of pulmonary hypertension in pediatric patients with SARS-CoV-2 infection ( 4 6 ). Olfe et al reported a 16-old-year patient with pulmonary hypertension and underlying mitral valve disease ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some previous reports of pulmonary hypertension in pediatric patients with SARS-CoV-2 infection ( 4 6 ). Olfe et al reported a 16-old-year patient with pulmonary hypertension and underlying mitral valve disease ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olfe et al reported a 16-old-year patient with pulmonary hypertension and underlying mitral valve disease ( 4 ). Morales-Demori et al reported on the status of COVID-19 morbidity in a pediatric pulmonary hypertension center ( 6 ). They found that of 23 children with COVID-19, 8 were hospitalized and that 3 of these patients required an intensification of targeted pulmonary hypertension therapy.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccines are advocated in adult patients with PH. The global COVID-19 pandemic is of particular concern to PH children due to immature immune systems and developmental comorbidities ( 18 ). However, data on the effectiveness and safety of COVID-19 vaccination in PH children are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A case report described ventilation-perfusion inhomogeneities as possible causes of dyspnea in children and adolescents after COVID-19 ( 10 ). In a cohort of four pediatric patients with pulmonary hypertension, Morales-Demori et al observed a mild decrease in lung function in three patients following SARS-CoV-2 infection ( 11 ). An Italian study examined the cardiopulmonary function of 115 athletes, most who were adolescents, after mild or asymptomatic SARS-CoV-2 infection before resuming sports activities and found slightly better FVC in mildly symptomatic rather than asymptomatic participants ( 12 ).…”
Section: Introductionmentioning
confidence: 99%